Product Innovation, Technology Utilization, and Global Market Competitiveness - Rahayu Pradikta, Aditya; Nurzaman, Kadar (Journal of Economicate Studies, 2022)
This study investigates the synergistic relationship between product innovation, technology adoption, and global market competitiveness, with a focus on emerging economies like Indonesia. Using a qualitative approach grounded in document and thematic analysis, the research explores how firms integrate digital technologies to enhance innovation outcomes and gain strategic advantages. The theoretical foundation draws from the Innovation Systems Approach, Dynamic Capabilities Framework, and Schumpeterian Competition Theory. Findings reveal that technology acts as a critical enabler of product innovation, while innovation itself is a key driver of firm-level competitiveness. However, systemic constraints—such as fragmented policy frameworks, inadequate R&D investment, and limited human capital—hinder broader innovation capacity in emerging contexts. The study offers a conceptual model that synthesizes innovation, technological infrastructure, and institutional dynamics, contributing both theoretical insights and actionable recommendations for businesses and policymakers aiming to strengthen competitiveness through innovation-led strategies.